Civilian Specialists at War - Phillips, Christopher (New Historial Perspectives, 2020)
The war of 1914-18 was the first great conflict to be fought between highly industrial societies able to manufacture and transport immense quantities of goods to the field of battle. In Civilian Specialists at War, Christopher Phillips examines the manner in which Britain's industrial society influenced the character and conduct of industrial warfare. This book analyses the multiple connections between the military, the government and the senior executives of some of pre-war Britain's largest companies. It illustrates the British army's evolving response to the First World War and the role to be played by non-military expertise in the prosecution of such a conflict. This study demonstrates that pre-existing professional relationships between the army, the government and private enterprise were exploited throughout the conflict. It details how civilian technologies facilitated the prosecution of war on an unprecedented scale, while showing how British experts were constrained by the political and military demands of coalition warfare. Civilian Specialists at War reveals that Britain's transport experts were a key component in the country's conduct of the First World War.